Advances on Natural Polyphenols as Anticancer Agents for Skin Cancer. (January 2020) - Sajadimajd, Soraya; Bahramsoltani, Roodabeh; Iranpanah, Amin; Kumar Patra, Jayanta; Das, Gitishree; Gouda, Sushanto; Rahimi, Roja; Rezaeiamiri, Elnaz; Cao, Hui; Giampieri, Francesca; Battino, Maurizio; Tundis, Rosa; et al.
Graphical abstract: The preventive effects of several polyphenols from herbs against skin cancer mediated by a number of signaling factors. Abstract: Polyphenols are one of most important phytochemicals distributing in herb plants, vegetables and fruits, which known as important anticancer agents. Given the high incidence and mortality of skin cancer, this study aimed to uncover the chemopreventive effects of polyphenols against skin cancer metastasis. Electronic databases including Scopus, PubMed, and Cochrane library were used to compile the literature from 2000 to August 2019. Only in vivo mechanistic studies with English full-texts were chosen for this review. Polyphenols were included in this study if they were administered in purified form; while total extract and fractions were excluded. Among the 8254 primarily selected papers, only a final number of 34 studies were included. The chemopreventive effects of polyphenols as anthocyanins, ellagitanins, EGCG, oleuropeindihydroxy phenyl, punicalagin, quercetin, resveratrol and theaflavin, were mainly examined in treatment of melanoma as the highly metastatic form of this cutaneous cancer. Those properties are mediated by modulation of angiogenesis, apoptosis, inflammation, metastasis, proliferation, pathways such as EGFR/MAPK, mTOR/PI3K/Akt, JAK/STAT, FAK/RTK2, PGE-2/VEGF, PGE-1/ERK/HIIF-1α, and modulation of related signals including NF-κB, P21 WAF/CIP1, Bim, Bax, Bcl2, Bclx, Bim, Puma, Noxa, ILs and MMPs. Chemopreventive effects of polyphenols are mediated by several signaling pathways against skin carcinogenesis and metastasis, implying the importance of polyphenols to open up new horizons in development of anti-skin cancer therapeutic strategies.